2011
DOI: 10.1039/c1sc00360g
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of carbon nanotubes and alkylated fullerenes: nanocarbon hybrid towards photovoltaic applications

Abstract: Taking advantage of the non-covalent interaction between alkyl chains and the sidewalls of a singlewalled carbon nanotube (SWCNT), a nanocarbon hybrid of SWCNT and a fullerene (C 60 ) derivative with long alkyl chains was constructed as a donor-acceptor pair for photovoltaics and nanodevice investigations. It was found that SWCNT could be mostly unbundled by the alkylated C 60 (1) and was well-dispersed in organic solvents. As a photoactive material, the resultant nanocarbon hybrid, 1-SWCNT, performed well in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
2
48
0
Order By: Relevance
“…One strategy to solubilize SWCNTs is to add surfactants such as sodium dodecyl sulfate (SDS) to water so that the surfactant molecules can adsorb onto the hydrophobic nanotube sidewall. [18][19][20] Aromatic chemicals can bind to graphene and SWCNTs via π-π stacking. 1D), thus forming stable nanotube solution.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…One strategy to solubilize SWCNTs is to add surfactants such as sodium dodecyl sulfate (SDS) to water so that the surfactant molecules can adsorb onto the hydrophobic nanotube sidewall. [18][19][20] Aromatic chemicals can bind to graphene and SWCNTs via π-π stacking. 1D), thus forming stable nanotube solution.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…As we reported recently, SWCNTs are mostly unbundled due to the assembly with 1 and well‐dispersed in organic solvents, i.e., chloroform and tetrahydrofuran (THF), because of a proper affinity of 1 , especially the attached long alkyl chains, toward the sidewalls of SWCNTs . Moreover, 1 also can align on the surface of graphite forming perfectly straight, submicrometer long C 60 nanowires, due to appropriate lattice matching between the graphite surface and the extended conformation of oligo‐methylene units .…”
mentioning
confidence: 92%
“…By analogy to the aforementioned graphene and metallic oxide composites, the hybrids of graphene and fullerenes is expected to create a new class of active materials with the strong electron‐accepting capability characteristic of fullerenes and the good charge transport properties associated with graphene. Similarly, our previous study has shown that the assembly of C 60 derivatives and single‐walled carbon nanotubes (SWCNTs) are promising for photovoltaics . Compared with SWCNTs, which are 1D and a mixture of semiconducting and metallic, graphene is 2D and has purely semimetal characteristics, thus providing a more preferred geometry and a simpler electronic structure to collaborate with C 60 , promoting the charge separation and charge transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Super capacitors Recent research investigations have shown that hybrid nano materials can generate synergistic and more exciting performance as electrode materials than the impact achieved by individual nano materials (Shen et al, 2011). A recent study revealed that a hybrid system composed of fullerene and graphene molecules conveyed a specific capacitance of 135.36 Fg -1 when used as electrode for super capacitors in contrast to the specific capacitance of pure graphene electrode ).…”
Section: Energy Materialsmentioning
confidence: 99%